Ultrashort optical pulse synthesis based on a two-step phase-amplitude hybrid algorithm - Dong, Xiaowei; Yu, Zhihui (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
Ultrashort optical pulses with user-desired temporal waveforms are widely applied in the areas of laser control and optical communication. In this paper, by combining the phase iteration and amplitude iteration, a two-step phase-amplitude hybrid algorithm for ultrashort optical pulse synthesis is proposed. Effectiveness of this proposed algorithm is proved by synthesizing two types of ultrashort optical pulses, including a single pulse with different temporal waveforms and a train of pulses with variable intensity envelopes. Compared with the conventional phase-only algorithm, the phase-amplitude hybrid algorithm can effectively reduce the influence of falling into local optimal solution caused by inappropriate initial chosen phase, thus achieving a better accuracy for synthesized pulses.
Optica Applicata, Vol. 54, 2024, nr 4, s. 541-550
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; pulse synthesize; hybrid algorithm; ultrashort optical pulse